إفريقيا ومؤشرات ما بعد الكولونيالية - بوصبعد. أحميد حمد (Aljameai, 2023)
المستخلص: أهتم فكر مابعد الكولونيالية بالدارسة، والبحث في قضايا جوهرية لها علاقة بالمجتمعات المستعمرة التي منها علي سبيل المثال لا الحصر : العنصرية، والهوية، والثقافة، واللغة، والزنوجة، والمرأة، والعنف وقد أشتغل مفكرو ما بعد الكولونيالية في كتاباتهم الفكرية والأدبية بالدفاع عن الهوية الوطنية، والثقافات المحلية للشعوب، ورفض النظرة العنصرية الإقصائية للمركزية الغربية، ودحض نظرياتها الفلسفية، ومغالطاتها الفكرية، في محاولة لتغيير تصوراتها ومفاهيمها الخاطئة ذات النزعة الاستعلائية المنغلقة على الذات التى تروج لفكرة تدني الأعراق والأجناس الغير أوروبية وتصورهم بأنهم أقل مرتبة، و غير قادرين على حكم انفسهم بأنفسهم؛ بهدف الهيمنة السياسية والاقتصادية، والثقافية، والنفسية على المجتمعات، وتحقيق تجانس الثقافات المحلية في الثقافة العالمية ؛ ما يعني القضاء على مجمل العادات والتقاليد والاعراف والدين، وموت اللغات والمعارف غير الغربية وهذا ماعبر عنه مفكرو مابعد الكولونيالية بالرفض الشديد بأن كل أمة لها خصوصيتها وثقافتها لاسيما في إفريقيا التي كانت مؤشرات فكر مابعد الكولونيالية قد بدأت بالظهور قبل نهاية المرحلة الكولونيالية. Abstract: Post-colonial thought is concerned with studying and researching fundamental issues related to colonial societies, including but not limited to: racism, identity, culture, language, Negritude, women, and violence. Post-colonial thinkers worked in their intellectual and literary writings by defending national identity and the local cultures of peoples, and rejecting the exclusionary racist view. Western centralism, and refute its philosophical theories and intellectual fallacies, in an attempt to change its misconceptions and misconceptions with an arrogant, self-enclosed tendency that promotes the idea of ​​the inferiority of non-European races and races and portrays them as inferior, and unable to govern themselves; With the aim of political, economic, cultural, and psychological domination over societies, Achieving homogeneity of local cultures in global culture; Which means the elimination of all customs, traditions, customs and religion, and the death of non-Western languages ​​and knowledge. This is what post-colonial thinkers expressed in their strong rejection that every nation has its own uniqueness and culture, especially in Africa, where indicators of post-colonial thought had begun to appear before the end of the colonial stage.